Call to Action Now: The Stockholm Declaration on Chemistry for the Future - Zuin Zeidler, Vânia G.; Szekely, Gyorgy; Bruijnincx, Pieter C. A.; Esteban, Jesús; Kapdi, Anant R.; Vidal, Juliana L.; Gross, Silvia; Liu, Huizhen; Nakamura, Masaharu; Slootweg, J. Chris (Sustainability & Circularity NOW, 2025)
The Stockholm Declaration on Chemistry for the Future presents a forward-looking vision and call for collective action, which is urgently needed today for the chemical sciences to drive sustainable development, involving all sectors, from science, industry, education and politics. It addresses important challenges such as environmental pollution and resource depletion, but also concrete ways to implement solutions for a better and more sustainable and ethical future. For Sustainability & Circularity NOW, the first journal to sign the Stockholm Declaration, the publication of this call to action is an important step that needs to be widely disseminated to our community and beyond.
Keywords: Stockholm declaration; Chemistry for the future; Collective action; Communication